Pengaruh Firm Size, Leverage, Dan Likuiditas Terhadap Nilai Perusahaan Manufaktur Yang Terdaftar di BEI Peiode 2018 – 2022 - Danni Arrafi; Atwal Arifin (Economics and Digital Business Review, 2024)
This research aims to determine the effect of company size, leverage and liquidity on company value. The research method used is a quantitative method. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sampling technique used in this research is purposive sampling consisting of 447 manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. This research shows that company size has no effect on company value. Leverage affects company value. Liquidity has no effect on company value.